(x+3/4)(x-4)=x²+3/4x-4x-3=x²-(13/4)x-3
if u want to know if your answer is right or false, it's easy
f(x)=x²-(13/4)x-3
and u can verify if f(4)=0 and f(-3/4)=0
Write a quadratic equation with -3/4 and 4 as its roots. Write the equation in form ax^2+bx+c=0, where a,b,and c are integers.
(x-p)(x-q)=0
(x--3/4)(x-4)=0
(x+3/4)(x-4)=0
x^2-3x+3=0(answer)
2 answers
if the roots are -3/4 and 4 then the factors that will form your equation are
(4x+3) and (x-4)
so (4x+3)(x-4) = 0 or
4x^2 13x - 12 = 0
(4x+3) and (x-4)
so (4x+3)(x-4) = 0 or
4x^2 13x - 12 = 0